Checking our balances: Louis Armstrong, Ralph Ellison, and Betty Boop - O'Meally, Robert G (Jazz Research Journal, 2004)
The key figure in the invention of the instrumental jazz solo, of the quality of inevitable-seeming momentum that the world calls swing, and of the relaxed, playful impulse to reinvent a song that is called jazz singing, Louis Armstrong is one of the inventors of jazz, a true revolutionary in art. Harder to evaluate with certainty are Armstrong’s cultural politics, the varied offerings and takings of his image and music, his significances as an American icon. Here I refer to “Ambassador Satch,” the tireless worker for the State Department and the one who stood up to Dwight Eisenhower at Little Rock; the man who surprised his white agent by saying angrily that Eisenhower, waffling in sync with Governor Faubus, had two faces and no heart. At the same time, I refer to the familiar comic image Armstrong began to offer the public, as early as the 1930s. What do we make of Armstrong’s semi-circular, shining smile? His signature flourish of a blazing white handkerchief? If in these familiar scenes what he wears is a comic mask, then what does it conceal? And how do we understand the meaning of the mask (or as Constance Rourke might say, the "double-mask") itself? What can Louis’s smiling face tell us about the man who took his stand against a U.S. president? How, if at all, does this complexly evocative face affect the way we hear his music? Is the comic act something he transcends in his creation of high art music—as the received wisdom would insist–or is the comedy part and parcel of an evidently contradictory artistic whole?